Political Economy after Neoliberalism - Neil Fligstein; Steven Vogel (Journal of Economic Sociology, 2021)
The Journal of Economic Sociology has published an article, "Political Economy after Neoliberalism," by one of the most influential figures in the tradition of New Economic Sociology, Neil Fligstein, and economic historian and comparative political economy scientist Steven Vogel. The article, originally published in Boston Review, was re-posted on the web¬site of the professional online community Economic Sociology & Politi¬cal Economy (ES/PE) and became one of the most-read texts in 2020. The authors offer a broad review of the current literature in the realm of eco¬nomic sociology, economic history, and political economy, and articulate a theoretical and practical alternative to the mainstream economic view of the nature of markets and the role of the state regulation of the economy. The text explores the causes and consequences of the crisis caused by the coronavirus pandemic and highlights the relationship between the crisis management measures adopted in different countries, their institutional arrangements, and the current balance of power. Fligstein and Vogel define three theoretical principles of the new political economy and then dem-onstrate its heuristic potential by analyzing the responses to the pandemic by the authorities and the United States and German markets. Strong at¬tention is paid to the analysis of the practical consequences of the politi¬cal economy project proposed by the authors: according to Fligstein and Vogel, accumulated knowledge allows the social sciences to participate in determining the preferred development scenarios of modern capitalism.